2002
DOI: 10.1002/bmc.170
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of reaction products of cocaine and hydrogen peroxide by high‐performance liquid chromatography/mass spectrometry

Abstract: The change of chemical structure of cocaine in the presence of hydrogen peroxide, a main component of hair dye and decolorant treatments, was studied. High-performance liquid chromatography/mass spectrometry (LC/MS) was used for the separation and identification of cocaine derivatives. After a mixture of cocaine and hydrogen peroxide solutions was incubated at 39 degrees C (this temperature is commonly used when the hair is treated with hair dye or decolorant) for 24 h, six reaction products were detected by L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…12 Furthermore, cocaine was converted directly to six compounds (ecgonine methyl ester, benzoylecgonine, ortho-, meta-and parahydroxycocaines and dihydroxycocaine) in the presence of hydrogen peroxide. 9 The fact that no intermediates could be detected in the two reaction mixtures with hydrogen peroxide suggested that morphine and codeine were directly converted to hydroxymorphine and hydroxycodeine, respectively. However, because minor reaction products of codeine with hydrogen peroxide were observed, it would be worthwhile to determine whether they include codeine N-oxide or morphine N-oxide.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Furthermore, cocaine was converted directly to six compounds (ecgonine methyl ester, benzoylecgonine, ortho-, meta-and parahydroxycocaines and dihydroxycocaine) in the presence of hydrogen peroxide. 9 The fact that no intermediates could be detected in the two reaction mixtures with hydrogen peroxide suggested that morphine and codeine were directly converted to hydroxymorphine and hydroxycodeine, respectively. However, because minor reaction products of codeine with hydrogen peroxide were observed, it would be worthwhile to determine whether they include codeine N-oxide or morphine N-oxide.…”
Section: Resultsmentioning
confidence: 99%
“…The LC/MS system and its conditions were the same as those in our previous reports, 8,9 except for the composition of the mixture of 10 mM ammonium acetate and methanol as the mobile phase (4:1 (v/v) for morphine analysis and 7:3 (v/v) for codeine analysis).…”
Section: High-performance Liquid Chromatography/mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Several analytical methods have been reported for the measurement of cocaine in various biological fluids including liquid chromatography (LC) (Raje et al, 2002), LC-mass spectrometry (MS; Fuh et al, 2001;Tanaka et al, 2002), LC-tandem mass spectrometry (LC-MS-MS; Xia et al, 2000;Dams et al, 2003), gas chromatography (GC; Virag et al, 1994;Farina et al, (Smirnow and Logan, 1996;Garside et al, 1997;Shimomura et al, 2001). Before the measurement of cocaine in biological fluids, sample preparation to remove proteins, such as protein precipitation (Smirnow and Logan 1996), liquid-liquid extraction (Garside et al, 1997;Farina et al, 2002;Raje et al, 2002) and solid-liquid extraction (Giovanni and Rossi 1994;Virag et al, 1994;Shimomura et al, 2001), has been used.…”
Section: Introductionmentioning
confidence: 99%
“…thioglycolate), bleaching (peroxide), dyeing (peroxide plus dyes), and chemical straightening (potassium hydroxide cream at very high pH). Although chemical interactions between the cosmetic agents and the analytes themselves are one aspect of such cosmetic treatments, an effect common to all is damage to the hair, especially disruption of the cuticular sheath resulting in increased porosity of the hair . In addition to the cosmetic treatments named above, hair can also exhibit damage from mechanical actions such as excessive brushing, rubber‐banding (e.g.…”
Section: Introductionmentioning
confidence: 99%